2020
DOI: 10.1111/aogs.13948
|View full text |Cite
|
Sign up to set email alerts
|

Induction of labor and nulliparity: A nationwide clinical practice pilot evaluation

Abstract: Introduction: Induction of labor has become an increasingly common obstetric procedure, but in nulliparous women or women with a previous cesarean section, it can pose a clinical challenge. Despite an overall expansion of medical indications for labor induction, there is little international consensus regarding the criteria for induction, or for the recommended methods among nulliparous women. In this light, we assessed variations in the practice of induction of labor among 21 birth units in a nationwide cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 26 publications
(40 reference statements)
1
13
0
1
Order By: Relevance
“…The increased rate of cesarean hysterectomy cannot be attributed to differences in the rates of uterine rupture or obstetrical hemorrhage, the two most common indications, as these were either not different or lower within the IOL group. Induction agents, such as prostaglandins and oxytocin, have also been associated with risk for uterine atony and rupture; however, we were unable to determine what agents were used for IOL [30][31][32][33][34] . Due to the nature of this study, the indication for cesarean hysterectomy could not be determined in this cohort, however, the overall rate was lower (0.01%) than recent rates reported with induction of labor among nulliparous women undergoing IOL (0.11%) and history of cesarean delivery 33 .…”
Section: Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased rate of cesarean hysterectomy cannot be attributed to differences in the rates of uterine rupture or obstetrical hemorrhage, the two most common indications, as these were either not different or lower within the IOL group. Induction agents, such as prostaglandins and oxytocin, have also been associated with risk for uterine atony and rupture; however, we were unable to determine what agents were used for IOL [30][31][32][33][34] . Due to the nature of this study, the indication for cesarean hysterectomy could not be determined in this cohort, however, the overall rate was lower (0.01%) than recent rates reported with induction of labor among nulliparous women undergoing IOL (0.11%) and history of cesarean delivery 33 .…”
Section: Main Findingsmentioning
confidence: 99%
“…Induction agents, such as prostaglandins and oxytocin, have also been associated with risk for uterine atony and rupture; however, we were unable to determine what agents were used for IOL [30][31][32][33][34] . Due to the nature of this study, the indication for cesarean hysterectomy could not be determined in this cohort, however, the overall rate was lower (0.01%) than recent rates reported with induction of labor among nulliparous women undergoing IOL (0.11%) and history of cesarean delivery 33 . Factors associated with risk for cesarean hysterectomy include high parity, maternal age, previous cesarean delivery, placental pathology, uterine atony and uterine rupture 34 .…”
Section: Main Findingsmentioning
confidence: 99%
“…Another Irish study comparing IOL and CS rates in ‘private versus public patients’ showed that the CS rate for all women following spontaneous onset of labour was 9.22%, compared with a CS rate of 31.25% following IOL [ 22 ], which lends credence to our participants’ views. This may be a uniquely Irish problem, perhaps due to different methods used for IOL, or differing gestational ages used as a criterion for induction, as IOL with an unripe cervix is more likely to lead to a ‘failed’ induction, a principal cause of CS [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…This could explain the stable/decreasing trend in CD among older women. The occurrence of the seven pregnancy complications increase with maternal age [ 6 ], which in turn is associated with increased risk of CD [ 26 ]. However, excluding these women from our analyses did not change CD trend across time or age groups.…”
Section: Discussionmentioning
confidence: 99%